Seasonal variations of 25-OH vitamin D serum levels in Multiple Sclerosis patients with relapse using MRI - Sharareh Sanei Sistani; Ali Moghtaderi; Ali Reza Dashipoor; Maryam Ghaffarpoor; Bahareh Heshmat Ghahderijani (PAGEPress Publications, 2019)
An increasing body of evidence suggests that low vitamin D (25-[OH]-D) concentrations is linked to increased activity in multiple sclerosis (MS) patients and MS relapse. Therefore, the current study was aimed to evaluate vitamin D serum concentrations and its possible seasonal variations among MS patients with relapse. This prospective, descriptive study was conducted on patients with MS relapse who referred to the neurology center of Ali ibn Abi Talib Hospital in Zahedan during one year. Magnetic Resonance Imaging (MRI)-Spine was performed for 90 patients and serum samples were collected from patient to measure serum vitamin D levels using RIA KIT. Furthermore, the Plaques in each patient's MRI were counted and then recorded. Descriptive and inductive statistics were conducted using statistical software. Our findings indicated a significant correlation between serum vitamin D level and cervical spinal cord plaques (p = 0.007, r=0.28), while no association was revealed between serum vitamin D level and number of brain plaque. Furthermore, a significant association was also observed between number of cervical spinal cord plaques and serum vitamin D levels. In addition, a reverse correlation was observed between number of cervical spinal cord plaques and serum vitamin D levels in spring. In autumn, there was a statistically significant relationship between number of brain plaque and serum vitamin D level. Additionally, a statistically significant relationship was found between serum vitamin D levels and number of plaques in winter. Our findings are in agreement with some previous studies that reported conflicting result, where the association of season with the prevalence of relapse cases cannot be verified. Although the mean serum levels of vitamin D are inversely correlated with the incidence of relapses in winter. However, the values obtained in the spring do not confirm such an inverse relationship.